Chlorofurancembranoids A and B: Novel cembranoids from octocoral Sinularia sp. (30th July 2022) - Tseng, Hsuan-Jung; Kuo, Liang-Mou; Chen, Po-Jen; Chen, Shun-Hua; Liu, Chia-Jung; Chien, Su-Ying; Tsai, Yu-Chi; Wu, Yu-Jen; Su, Tzu-Rong; Sung, Ping-Jyun
Abstract: Two novel chlorine-containing cembranoids, chlorofurancembranoids A (1 ) and B (2 ), were isolated from an octocoral identified as Sinularia sp. The structures of 1 and 2 were elucidated using spectroscopic methods, and the absolute configuration of 1 was further confirmed by single-crystal X-ray diffraction analysis. Cembranoid 2 showed cytotoxicity towards human promyelocytic leukemia HL-60 cells, with an IC50 value of 3.67 μM. Graphical abstract: Image 1